Pemahaman Pemasaran Digital dan Sustainability pada UMKM dan Dampaknya terhadap Kinerja UMKM - Kasim, Erlynda Yuniarti; Martana, Cynthia Riyanti (Papanda Publisher, 2024)
The purpose of this study is to examine the impact of digital marketing and sustainability practices on the performance of Micro, Small, and Medium Enterprises (MSMEs) in a specific region. The research addresses the problem of how these two factors influence business performance, aiming to provide actionable insights for MSME managers. The study utilized a quantitative research method, employing a structured questionnaire as the primary instrument. A total of 117 MSME owners or managers from the specified region participated as research subjects. Data were analyzed using multiple linear regression to assess the relationship between digital marketing, sustainability, and business performance. The results indicate that both digital marketing and sustainability practices significantly contribute to the improvement of MSME performance. Specifically, effective digital marketing strategies, such as optimizing social media and e-commerce platforms, were found to enhance business outcomes by expanding customer reach and increasing sales efficiency. Similarly, sustainability practices, including the use of environmentally friendly materials and responsible waste management, were shown to improve operational efficiency, customer satisfaction, and overall business reputation. The study concludes that integrating both digital marketing and sustainability into business strategies is crucial for MSMEs to achieve better performance and long-term competitiveness. These findings suggest that MSMEs should prioritize investments in digital marketing and adopt sustainable practices to strengthen their market position.